A phase II study of buparlisib in relapsed or refractory thymomas - Abu Zaid, Mohammad I.; Radovich, Milan; Althouse, Sandra; Liu, Hao; Spittler, Aaron J.; Solzak, Jeffrey; Badve, Sunil; Loehrer, Patrick J. (Frontiers in Oncology, 2022)
PURPOSE: To investigate the efficacy and safety of buparlisib, an oral pan-PI3K inhibitor, in relapsed or refractory thymomas. Methods: This was a single center, single arm, open label phase II trial of buparlisib in patients with recurrent thymoma who have progressed after at least one prior line of treatment. The primary endpoint was objective response rate (complete response [CR] + partial response [PR]). Secondary endpoints included toxicity; progression free survival (PFS); overall survival (OS); disease control rate (DCR), i.e., the percentage of patients who achieve either PR or CR or stable disease [SD] for at least 4 months. Results: Between 10/13/2014 and 1/18/2017, 14 patients with stage IV disease were enrolled. Median age was 58y (23–74). 71% were females and 71% white. All patients had WHO B2 (29%) or B3 (71%) thymoma. Patients received buparlisib for a median of 4.5m (2–33). At a median follow up of 16.6m (2.4–31.3), onr patients (7%) achieved a PR. DCR was 50%. Median PFS was 11.1m (95% CI 2.9 – 18.8). Median OS, updated as of March, 2021 was 22.5m (10.7–31.3). Most common grade 3-4 adverse events related to buparlisib were dyspnea (21%), rash (14%), elevated transaminases (14%), cough (7%), pneumonitis (7%), anxiety (7%), fatigue (7%) and hyperglycemia (7%). Reasons for treatment discontinuation included progression of disease (n= 5), rash (n=4), pulmonary toxicity (n=3), sinusitis (n=1), and disseminated toxoplasmosis plus autoimmune cholangitis (n=1). As of 3/2021, 8 patients have died, 7 due to disease progression and 1 due to central nervous system toxoplasmosis and autoimmune cholangitis. Conclusion: Buparlisib showed modest activity in patients with relapsed or refractory thymomas. Further investigation of PI3K pathway targeted therapy in thymoma is warranted. (clinicaltrials.gov ID: NCT02220855).